Study on the antibacterial activity of liquid hand-wash containing triclosan against clinical samples - Mustafa, Fuad (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2017.